Yield and Water Use Efficiency of Potato under Alternate Furrows and Deficit Irrigation - Kassu Tadesse Kassaye; Wubengeda Admasu Yilma; Mehiret Hone Fisha; Dawit Habte Haile (International Journal of Agronomy)
The benefits of water-saving techniques such as alternate furrow and deficit irrigations need to be explored to ensure food security for the ever-increasing population within the context of declining availability of irrigation water. In this regard, field experiments were conducted for 2 consecutive dry seasons in the semiarid region of southwestern Ethiopia and investigated the influence of alternate furrow irrigation method with different irrigation levels on the yield, yield components, water use efficiency, and profitability of potato production. The experiment comprised of 3 irrigation methods: (i) conventional furrow irrigation (CFI), (ii) alternate furrow irrigation (AFI), and (iii) fixed furrow irrigation (FFI) combined factorially with 3 irrigation regimes: (i) 100%, (ii) 75%, and (iii) 50% of the potato water requirement (ETC). The experiment was laid out in randomized complete block design replicated thrice. Results revealed that seasonal irrigation water applied in alternate furrows was nearly half (170 mm) of the amount supplied in every furrow (331 mm). Despite the half reduction in the total amount of water, tuber (35.68 t ha−1) and total biomass (44.37 t ha−1) yields of potato in AFI did not significantly differ from CFI (34.84 and 45.35 t ha−1, respectively). Thus, AFI improved WUE by 49% compared to CFI. Irrigating potato using 75% of ETC produced tuber yield of 35.01 t ha−1, which was equivalent with 100% of ETC (35.18 t ha−1). Irrigating alternate furrows using 25% less ETC provided the highest net return of US$74.72 for every unit investment on labor for irrigating potato. In conclusion, irrigating alternate furrows using up to 25% less ETC saved water, provided comparable yield, and enhanced WUE and economic benefit. Therefore, farmers and experts are recommended to make change to AFI with 25% deficit irrigation in the study area and other regions with limited water for potato production to improve economic, environmental, and social performance of their irrigated systems.